Medicinal plants used by Tibetans in Shangri-la, Yunnan, China - Yang Chunyan; Dao Zhiling; Liu Yanchun; Liu Yitao; Long Chunlin (BMC, 2009)
Abstract Background Medicinal plants used by the local people in Xizang (Tibet) have been investigated since the 1960s. The others out of Xizang, however, have been less understood, although they may be easily and strongly influenced by the various local herbal practices, diverse environments, local religious beliefs and different prevalent types of diseases. In 2006, two ethnobotanical surveys were organized in the county of Shangri-la, Yunnan Province, SW China, to document the traditional medicinal plants used by the Tibetan people. Methods After literature surveying, four local townships were selected to carry out the field investigation. Three local healers were interviewed as key informants. The methods of ethnobotany, anthropology and participatory rural appraisal (PRA) were used in the field surveys. Plant taxonomic approach was adopted for voucher specimen identification. Results Sixty-eight medicinal plant species in 64 genera of 40 families were recorded and collected. Among them, 23 species were found to have medicinal values that have not been recorded in any existing Tibetan literatures before, and 31 species were recorded to have traditional prescriptions. Moreover, the traditional preparations of each species and some folk medicinal knowledge were recorded and analyzed. These traditional prescriptions, preparations, new medicinal plants and folk medicinal knowledge and principles were discovered and summarized by local traditional Tibetan healers through times of treatment practices, and were passed down from generation to generation. Conclusion As a part of the cultural diversity of Tibetan community, these traditional medicinal knowledge and experiences may provide data and information basis for the sustainable utilization and development of Tibetan medicine, and may contribute to the local economic development. However, for many reasons, they are disappearing gradually as time goes by. Our study showed that there were abundant traditional Tibetan medicinal prescriptions and using methods. It implies that more Tibetan medicinal plants and traditional knowledge can be discovered. Further research should be done to save the wealth of these traditional medicinal knowledge and experiences before they are dying out.